Organoleptic evaluation and chemical tests of various formulations of kencur drink (Kaemfelia galanga L.): efforts to find the best formulation to increase body immunity (Talenta Publisher, 2023)
Kencur drink is one of the traditional drinks that has been known to be popular and has become an icon for daily healthy drinks. Kencur drink is very useful in preventing and treating diarrhea in Indonesia, can prevent colds and flu. Kencur can also prevent cancer, stop vomiting, prevent and treat fungi, lower cholesterol and improve appetite. Therefore, various ways are done so that this kencur drink remains a healthy daily drink, such as giving a mixture of other ingredients, one of which is the provision of stevia leaf extract. There is also the addition of lemon, brown sugar, and others. Methods in the study with the addition of stevia extract were increased from groups one to six. While other compositions remain such as kencur, lemon and brown sugar. From the results of the study it was obtained that the addition of stevia leaf extract was the highest most preferred and contained vitamin C which was more abundant with other groups. It was concluded that giving stevia leaf extract as much as 24.24% became a favorite drink and had the highest vitamin C content